PROSPEK EKSPOR KOPI ARABIKA ORGANIK BERSERTIFIKAT DI KABUPATEN ACEH TENGAH - Lukman Hakim; Andika Septian (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2011)
Export Prospects the Certified Organic Coffee Arabica at Central Aceh DistrictABSTRACT. This study was aimed to determine the export prospects of the certified organic coffee Arabica at Central Aceh district in the future. The object of study was secondary data related to export activity of the certified organic coffee Arabica in that district. The sampling method was a periodic data (time series), and trend analysis. The result showed that the export activity of the certified organic coffee Arabica has been started since August 2006 concurrently with receiving a certification from